Ovarian collision tumour: a rare case of serous cystadenoma with granulosa cell tumor of ovary - Vernekar, Veena M.; Gollar, Prashanth F.; Sana, Syeda; Sampath Kumar, Sreelatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
A collision tumor is the coexistence of two distinct tumours without any histological intermixing in the same organ or tissue. Each component of collision tumors occurs coincidently and biologic behaviour depends on their own tumor characteristics. A 48 year aged P2L2 women with pain abdomen since 15 days, on abdominal examination-a cystic mass occupying left iliac fossa present, bimanual examination a cystic mass measuring 13x10x8 cm in size, felt separately from the uterus. Sonography of abdomen and pelvis revealed a large cyst in the right adnexa 11.5x10.5x9.5 cm extending upto umbilical region. The serum tumor markers were within the normal range. Patient complained of severe pain abdomen on next day. Emergency laparotomy was done. Left ovarian cyst measuring 13x12x7 cm in size with one loop of torsion seen. Left salphingo-ophorectomy done and specimen sent for frozen section. It reported as serous cystadenoma of left ovary. Then proceeded to total abdominal hysterectomy with right salphingo-oophorectomy. Histopathology reported Serous cystadenoma with focal Granulosa cell tumour- left ovary. Patient was followed up with serum inhibin and CECT abdomen. The demographic factors, presentations and diagnosis of collision tutors are as similar as with single ovarian tumours. It is important for gynaecologist, radiologist and pathologist to be aware of occurrence of collision tumours. Histopathogical diagnosis of such neoplasms becomes very important, to provide appropriate treatment based on the individual biological characteristics of each component of collision tumours.